2008
DOI: 10.1074/jbc.c800100200
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric CFTR in Plasma Membranes in Live Cells Revealed by Single Molecule Fluorescence Imaging

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-regulated chloride channel. There is indirect and conflicting evidence about whether CFTR exists in cell membranes as monomers, dimers, or higher order oligomers. We measured fluorescence intensities and photobleaching dynamics of distinct fluorescent spots in cells expressing functional CFTR-green fluorescent protein (GFP) chimeras. Intensity analysis of GFP-labeled CFTR in live cells showed singlecomponent distributions with mean intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Based on the fact that the fluorescent intensity of the EGFP monomer is close to the intensity of pHluorin under the environment of pH 7.4 (25,30,31), we compared the fluorescent intensity of EGFP monomers to the intensity of single events of pH-NR1 under TIRFM. EGFP monomers were confirmed by their single-step photobleaching property and blinking dynamics (21,23,32,33) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 77%
“…Based on the fact that the fluorescent intensity of the EGFP monomer is close to the intensity of pHluorin under the environment of pH 7.4 (25,30,31), we compared the fluorescent intensity of EGFP monomers to the intensity of single events of pH-NR1 under TIRFM. EGFP monomers were confirmed by their single-step photobleaching property and blinking dynamics (21,23,32,33) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 77%
“…The assembly state of another ABC protein, the cystic fibrosis transmembrane conductance regulator (CFTR), was also controversial as a result of indirect evidence that suggested CFTR could exist as monomers, dimers, or higher-order oligomers. However, fluorescence-intensity measurement and analysis of photobleaching dynamics of CFTR fused with GFP by Haggie and Verkman revealed that CFTR is monomeric (32), where single-molecule fluorescence imaging was beneficial for verifying the oligomeric state of a membrane protein as well as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found here that GFP labeling of AQP4 isoforms at their C termini or in their extracellular loops did not impair their plasma membrane targeting or the ability of M23 to form OAPs. There are several other examples of successful insertions of GFP in internal loops in membrane proteins, including CFTR (cystic fibrosis transmembrane conductance regulator) (21) and the vesicular glutamate transporter VGLUT1 (23). It is thought that the proximity of the N and C termini of GFP and its tight ā¤-barrel structure allow its insertion in internal loops with minimal perturbation of protein folding or structure.…”
Section: Discussionmentioning
confidence: 99%
“…Images were processed, and backgroundsubtracted area-integrated intensities were analyzed as described previously (21). Time-lapse images of AQP4 OAPs in live cells were acquired at three frames/min for up to 3 h, with the excitation laser shuttered between image acquisitions.…”
Section: Methodsmentioning
confidence: 99%